The role of public relations strategies in shaping or reflecting national identity : a content analysis of the speeches of two Governors-General in New Zealand : a 219.899 presented in partial fulfilment of the requirements for the degree of Master of Communication at Massey University, Auckland, New Zealand - Brunzel, Natalie Yvette (Massey University, 2015)
This thesis focuses on the role public relations strategies perform in reflecting or shaping New Zealand identity by using content analysis to examine the speeches of two Governors-General from different eras. The core data which is the focus of this analysis comprises the swearing-in, Waitangi Day and Anzac Day speeches delivered by Lord Cobham (1957-1962) and Sir Jerry Mateparae (2011-present). Cobham, an English aristocrat, became Governor-General a decade after New Zealand commenced governing independently and ended a decade before Britain joined the European Union. It signals a time when New Zealand prosperity hinged on Britain and represents a moment in time when British ideology was strongly linked to New Zealand identity. Mateparae, a New Zealander with Maori ancestry, took office at a time of increased debate surrounding the nation’s identity in relation to the flag. A comparison between the two offers insight into the fluidity of the nation’s identity. Amidst the debate of the flag is an underlying questioning of the need for New Zealand to maintain its link with Britain. The Governor-General’s role is ceremonial, constitutional and community focused. This means the incumbent performs a key part, by delivering speeches, in the rituals which symbolise the nation’s identity (e.g., Waitangi Day). It is important to understand whether the Governor-General is shaping or reflecting the New Zealand national identity as the role requires s/he be apolitical. Qualitative content analysis was used to analyse the data applying the rhetorical theory framework. The findings suggest that two Governors-General have used public relations strategies to primarily reflect the dominant publics’ national identity, within the existing social hierarchy. The findings of this research could be furthered by an analysis of what New Zealanders perceive to be the role of the Governor-General and who s/he reflects compared with the findings of this thesis which emphasised that only the views of the influential publics were being reflected.
Keywords: Cobham, Charles John Lyttelton, Viscount, 1909-1977 Oratory; Mateparae, Jerry Oratory; Mass media and nationalism; Public relations; Governors general; New Zealand; Public relations; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Human communication